Mid-infrared Polarized Emission from Black Phosphorus Light-Emitting Diodes - Wang, Junjia; Rousseau, Adrien; Yang, Mei; Low, Tony; Francoeur, Sébastien; Kéna-Cohen, Stéphane (Nano letters, 2020)
We demonstrate a mid-infrared light-emitting diode based on the 2D semiconductor black phosphorus (BP). The device is composed of a mechanically exfoliated BP/molybdenum disulfide heterojunction. Under forward bias, it emits polarized electroluminescence at λ = 3.68 μm, with room-temperature internal and external quantum efficiencies of ∼1% and ∼0.03%, respectively. In our structure, outcoupling losses are dominated by radiation toward the high refractive index substrate. The ability to tune the bandgap of BP and consequently its emission wavelength with layer number, strain, and electric field make these LEDs particularly attractive for heterointegration into mid-infrared photonic platforms.